The Effect of Financial Literacy and Financial Attitude on Financial Management Behavior in Generation Z in Bekasi Regency - Yosida Rahmadani; Ari Sulistyowati; Christophorus Indra Wahyu; Tyna Yunita (Draf Solusi Indonesia, 2023)
The Effect of Financial Literacy and Financial Attitude on Financial Management Behavior in Generation Z in Bekasi Regency. This research is to measure the effect of Financial Literacy and Financial Attitude on Financial Management Behavior in Generation Z in Bekasi Regency. This research is quantitative research where the object used by Generation Z is Papan Indah Housing, Bekasi Regency. The number of samples used in this study was 122 respondents. Data collection techniques used questionnaires and data processing and hypothesis testing using SmartPLS 4.0. The results of this study explain that Financial Literacy has a significant positive effect on Financial Management Behavior, and the Financial Attitude variable has a significant positive effect on Financial Management Behavior